Adaptacyjne metody jądrowe w regresji - Trzęsiok, Joanna (Adaptive Kernel Methods of Regression, 2005)
In this article kernel methods for regression are presented. These methods are based on theory of local estimation when one needs to estimate an unknown function only at a single point. The methods don't need the analytic form of the model, so they are the adaptive methods. An example is given for illustration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 493-500